Correction: Establishment of a Canine Rabies Burden in Haiti through the Implementation of a Novel Surveillance Program. - Ryan M Wallace; Hannah Reses; Richard Franka; Pierre Dilius; Natael Fenelon; Lillian Orciari; Melissa Etheart; Apollon Destine; Kelly Crowdis; Jesse D Blanton; Calvin Francisco; Fleurinord Ludder; et al. (Public Library of Science (PLoS), 2016)
[This corrects the article DOI: 10.1371/journal.pntd.0004245.].